Alright so first let's look at what we have.
First work away the brackets, for example;
$$3(x-4) = 6(2x+1) \Rightarrow 3x-12 = 12x+6$$
Now substract $$12x$$ from both sides
$$-9x-12 = 6$$
Add $$12$$ to both sides
$$-9x = 18$$
Divide both sides by -9
$$x = -2$$
so now first well multiply 3 by x and 4 and 6 by 2x and 1 .
ur right reinout-g , first i did it ur way like my last step was -9=18
but then i didnt do it this way ! ah now ill never ever take chances as they always turn out scaaaaaaaarrrry !
Reinout is right!
Use your edit button to fix your post (minus signs are missing)
also get rid or the extra = signs at the beginning of your lines and then I'll give you thumbs up!
It would be even better Rosala if you deleted the equal signs at the begining of each line.
There should only be one equal sign per line!
Oh Reinout - I love your rooster - he is VERY talented!
now i hope there wouldnt be anything to point out !
and reinout good pics !
thanks melody and reinout for the help of improvement of my answer !
i would like to give bothof u a thumbs up !